The Effect of Audiovisual Health Education on Cervical Cancer Early Detection and Prevention Knowledge Among Female Students at SMAK Sint Carolus Kupang - Feliksia Bas; Simon Kleden; Antonia Hamu (Poltekkes Kemenkes Kupang, 2024)
Cervical cancer remains a major global health concern, particularly in Indonesia, where it accounts for a significant proportion of cancer cases among women. This study aimed to determine the effect of audiovisual-based health education on knowledge regarding early detection and prevention of cervical cancer among female students at Sint Carolus Kupang Catholic High School. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed. The research was conducted at the school in 2023, involving all 35 Grade XI female students as the sample, divided into three study groups. The independent variable was health education using audiovisual media, and the dependent variable was students’ knowledge level. Data were collected through structured questionnaires administered before and after the intervention and analyzed using the Wilcoxon signed-rank test. Results showed a statistically significant increase in knowledge scores after the intervention (p = 0.000 < 0.05). The findings indicate that audiovisual health education effectively improves students’ understanding of cervical cancer prevention and early detection. It is recommended that the school integrate such educational strategies into its health curriculum to promote long-term awareness and preventive behavior among adolescents.